А) (-5; 4), (-7; 4), (-9; 6), (-11; 6), (-12; 5), (-14; 5), (-12; 4), (-14; 3), (-12; 3), (-11; 2), (-10; 2),
(-9; 1), (-9; 0), (-8; -2), (0; -3), (3; -2), (19; -2), (4; 0), (19; 4), (4; 2), (2; 3), (6; 9), (10; 11), (3; 11), (1; 10), (-5; 4), глаз (-10,5; 4,5).
б) (-2;2), (-2;-4), (-3;-7), (-1;-7), (1;4), (2;3), (5;3), (7;5), (8;3), (8;-3), (6;-7), (8;-7), (10;-2), (10;1),
(11;2,5),(11;0), (12;-2), (9;-7), (11;-7), (14;-2), (13;0), (13;5), (14;6), (11;11), (6;12), (3;12), (1;13), (-3;13),
(-4;15),(-5;13), (-7;15), (-8;13), (-10;14), (-9;11), (-12;10), (-13;9), (-12;8), (-11;9), (-12;8), (-11;8), (-10;7),
(-9;8),(-8;7), (-7;8), (-7;7), (-6;7), (-4;5), (-4;-4), (-6;-7), (-4;-7), (-2;-4), глаз (-7;11)
cos(α+β)+2sinαsinβ=cosαcosβ−sinαsinβ+2sinαsinβ=
cosαcosβ+sinαsinβ=cos(α−β)
если \alpha -\beta=\piα−β=π , то cos(\alpha -\beta ) =cos\pi =-1.cos(α−β)=cosπ=−1.
б)
\frac{sin^{2}\alpha +sin(\pi-\alpha)cos (\frac{\pi }{2} -\alpha) }{tq(\pi+\alpha)ctq( \frac{3\pi }{2} -\alpha ) } = \frac{sin^{2}\alpha +sin\alpha*sin\alpha }{tq\alpha*tq\alpha } =\frac{2sin^{2} \alpha }{tq^{2} \alpha } =\frac{2sin^{2}\alpha }{\frac{sin^{2} \alpha }{cos^{2} \alpha } } =2cos^{2} \alpha .
tq(π+α)ctq(
2
3π
−α)
sin
2
α+sin(π−α)cos(
2
π
−α)
=
tqα∗tqα
sin
2
α+sinα∗sinα
=
tq
2
α
2sin
2
α
=
cos
2
α
sin
2
α
2sin
2
α
=2cos
2
α.
в)
cos7xcos6x+sin7xsin6x=cos(7x-6x)=cosx.cos7xcos6x+sin7xsin6x=cos(7x−6x)=cosx.